Gorivne celice s trdnim elektrolitom - Panjan, Peter (Vakuumist, 1997)
This paper reviews the physics and chemistry of high temperature solid oxide fuel cells. The development and technology of this type of fuel cells is described. The emphasis is given to the discussion of component materials (especially ZrO2 electrolyte, nickel/ZrO2 cerment anode, LaMnO3 cathode, and LaCrO3 interconnect) and gas reactions at the electrodes.
Keywords: elektrokemija; gorivne celice; izdelava